Mineralocorticoid and angiotensin II type 1 receptors in the subfornical organ mediate angiotensin II – induced hypothalamic reactive oxygen species and hypertension. (4th August 2016) - Wang, Hong-Wei; Huang, Bing S.; White, Roselyn A.; Chen, Aidong; Ahmad, Monir; Leenen, Frans H.H.
Graphical abstract: Schematic outline of the interactive role of central aldosterone-MR signaling and AT1 R-ROS signaling pathways for progressive hypertension by circulating Ang II. Direct Ang II-AT1 R-ROS signaling from SFO to PVN appears essential, but not sufficient for Ang II-induced hypertension. Amplification by aldosterone-MR signaling in the SFO and PVN is needed (as indicated by red line and arrows). Highlights: (Modest) increases in plasma Ang II play an important role in hypertension and heart failure. Circulating Ang II increases ROS in the SFO, PVN, SON and RVLM in a nucleus-specific pattern. Knockdown of MR or AT1 R in the SFO prevents sc Ang II-induced ROS in the PVN and RVLM, and hypertension. Persistent brain angiotensinergic pathway activation by plasma Ang II depends on Aldo-MR in the SFO. Abstract: Activation of angiotensinergic pathways by central aldosterone (Aldo)-mineralocorticoid receptor (MR) pathway plays a critical role in angiotensin II (Ang II)-induced hypertension. The subfornical organ (SFO) contains both MR and angiotensin II type 1 receptors (AT1 R) and can relay the signals of circulating Ang II to downstream nuclei such as the paraventricular nucleus (PVN), supraoptic nucleus (SON) and rostral ventrolateral medulla (RVLM). In Wistar rats, subcutaneous (sc) infusion of Ang II at 500 ng/min/kg for 1 or 2 weeks increased reactive oxygen species (ROS) as measured by dihydroethidium (DHE) staining in a nucleus – specific pattern. Intra-SFO infusion of AAV-MR- or AT1a R-siRNA prevented the Ang II-induced increase in AT1 R mRNA expression in the SFO and decreased MR mRNA. Both MR- and AT1a R-siRNA prevented increases in ROS in the PVN and RVLM. MR- but not AT1a R-siRNA in the SFO prevented the Ang II-induced ROS in the SON. Both MR- and AT1a R-siRNA in the SFO prevented most of the Ang II-induced hypertension as assessed by telemetry. These results indicate that Aldo-MR signaling in the SFO is needed for the activation of Ang II-AT1 R-ROS signaling from the SFO to the PVN and RVLM. Activation of Aldo-MR signaling from the SFO to the SON may enhance AT1 R dependent activation of pre-sympathetic neurons in the PVN.